Pengaruh Budaya Organisasi, Lingkungan Kerja dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan Pada PT Panca Putra Madani - Sigit Purnomo; Agung Tri Putranto (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2020)
The purpose of this research is to determine the influence between theories and facts related to the independent variables, namely organizational culture, work environment and work discipline as well as the dependent variable, namely job satisfaction. The quantitative method approach with the form of cause and effect is associative (causal). The total population and sample of this research were 70 respondents, which means that all populations will be made respondents using non-probability sampling, which is commonly referred to as saturated samples. In analyzing the data, the writer uses inferential statistics, namely by testing the feasibility of the data to be studied which includes the validity test (validity) and the reliable test (reliability), then the classical assumption test such as normality test, multicollinearity test and heteroscedasticity test. As for the hypothesis testing using the Fisher test (F test) and t test (t test), then testing the coefficient of determination, as well as testing multiple linear regression analysis. The value obtained in this study, Hypothesis testing, obtained that the F test (simultaneously) the independent variables (organizational culture, work environment and work discipline) get a greater value than the table which means that there is a positive and significant influence on the dependent variable (Job Satisfaction). where the value of Fcount > Ftable (9.337> 2.51). The results of the partial test of organizational culture on job satisfaction have a positive and significant effect, where the value of tcount > t table (3.325> 1.99). Work environment on job satisfaction has a positive and significant effect, where the value of tcount > ttable (4.264> 1.99). Work discipline on job satisfaction has a positive and significant effect, where the value of tcount > ttable (2.364> 1.99). The contribution of the independent variables, namely organizational culture, work environment and work discipline on job satisfaction, shows the Adjusted R Square figure of 0.266 or 26.6%, where 73.4% are other components outside of this research. And finally, in the multiple linear regression equation test it produces Y = 7.438 + 0.087X1 + 0.137X2 + 0.089X3. Abstrak Penelitian ini bertujuan untuk mengetahui serta membuktikan kesesuaian antara teori dengan fakta terkait seberapa besar variabel-variabel bebas budaya organisasi, lingkungan kerja dan disiplin kerja berpengaruh terhadap variabel terikat kepuasan kerja. Pendekatan metode kuantitatif dengan bentuk sebab akibat yaitu asosiatif (kausal). Sampel berdasarkan populasi yang ada berjumlah 70 responden, di mana seluruh populasi dijadikan sampel dengan teknik nonprobability sampling yaitu sampel jenuh. Teknik analisis data menggunakan statistik inferensial (parametris) dengan uji kelayakan data meliputi uji validitas dan uji reliabilitas, uji asumsi klasik yaitu normalitas, multikolinieritas, heteroskedastisitas. Adapun uji hipotesis dilakukan uji F, uji uji t, analisis koefisien determinasi, dan analisis regresi berganda. Hasil penelitian berdasarkan rangkaian uji didapat uji F (simultan) variabel bebas (budaya organisasi, lingkungan kerja dan disiplin kerja), berpengaruh positif dan signifikan terhadap variabel terikat (kepuasan kerja) di mana nilai Fhitung>Ftabel (9.337>2.51). Hasil uji parsial budaya organisasi terhadap kepuasan kerja mempunyai pengaruh positif dan signifikan, di mana nilai thitung>ttabel (3.325>1.99). Lingkungan Kerja terhadap kepuasan kerja mempunyai pengaruh positif dan signifikan, di mana nilai thitung>ttabel (4.264>1.99). Disiplin kerja terhadap kepuasan kerja berpengaruh positif dan signifikan, di mana nilai thitung>ttabel (2.364>1.99). Besaran sumbangsih variabel bebas yaitu budaya organisasi, lingkungan kerja dan disiplin kerja terhadap kepuasan kerja didapat angka Adjusted R Square sebesar 0.266 atau 26,6% di mana 73,4% adalah faktor-faktor lain yang tidak teridentifikasi. Sedangkan persamaan regresi didapat Y= 7.438 + 0.087X1 + 0.137X2 + 0,089X3. Kata Kunci : Budaya Organisasi, Lingkungan Kerja, Disiplin Kerja, kepuasan Kerja